Energy Storage Systems Planning in the Electric Distribution System Considering the Grow of PV Penetration - Martinez, Norberto A. [UNESP]; Orfanoudakis, Stavros; Vergara, Pedro P.; Franco, John F. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2024)
Interest in integrating distributed energy resources (DERs) into the electric distribution system (EDS) is growing due to the economic and operational benefits that DERs can provide. Consumer-sited photovoltaic (PV) generation is one of those DERs that have been penetrating the EDS over the years; the owner can sell the energy surplus to the EDS, and for the EDS operator it brings the advantage of clean energy from solar irradiation; since the EDS operator doesn't have control of it, the growing of the penetration can leading into technical problems to the EDS. Energy storage systems (ESS) can be used to manage non-dispatchable renewable energy providing ancillary services to the EDS like peak shaving and voltage regulation. However, investors for the ESS planning (allocation and sizing) must consider their cost, EDS constraints, and the future scenarios of PV penetration and uncertainties inherent to the EDS; for this purpose, a stochastic mixed integer linear programming model for the ESS planning is presented integrating a temporal method to model the PV penetration growth over the years. The decision variables are the size and the EDS node where the ESS should be connected. The model is implemented in AMPL and the optimal solution is found with CPLEX for a case study based on the IEEE 33 node test system.
Keywords: electrical distribution system; energy storage systems; mathematical programming model; photovoltaic generation